Qualidade física de um Latossolo Vermelho em recuperação há dezessete anos - Bonini, Carolina S. B. [UNESP]; Alves, Marlene C. [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
The bulk density and resistance to penetration as indicators of recovery were studied with the objective to investigate the physical quality of a Red Latosol (Oxisol) under restoration for 17 years using green manures, soil correction, gypsum and pasture. The experimental design was a completely randomized with nine treatments and four replications. The treatments were: control (tilled soil without crop); Stizolobium aterrium; Cajanus cajan until 1994 and then substituted by Canavalia ensiformis; lime+S. aterrimum; lime+C. cajan until 1994 and then substituted by C. ensiformis; lime+gypsum+S. aterrimum; lime+ gypsum+C. cajan until 1994 and then substituted by C. ensiformis, the treatments were installed in 1992 and remained for seven years, in 1999 Brachiaria decumbens was planted; two other controls (native vegetation and exposed soil) were also used to compare. Bulk density, resistance to penetration and soil moisture were evaluated. The results were analyzed performing analysis of variance and Tukey test at probability of 5% to compare means. The treatments of reclamation are improving the physical qualities of soil and the results of treatment with C. cajan/C. ensiformis, lime and gypsum attained physical conditioning similar to soil under natural conditions.
Physical quality of oxisol under reclamation for 17 years
Keywords: loan area; soil degradation; green manure; organic matter